Instagramabilna estetika - Senka Božić- Vrbančić ([sic])
This article examines the aesthetic category of the ‘Instagrammable’ and explores what it means for destinations like Telašćica Nature Park to be seen as Instagram Hot Spots. I begin by addressing issues arising from the spread of social media platforms like Instagram, particularly the role of marketing and the subtle operations of digital algorithms. From there, I explore the shifting notion of “authenticity” in tourist sites like Telašćica, where the Instagrammable aesthetic takes root, redefining what it means for a place to be “seen.” I argue that ‘Instagrammable’ as an aesthetic category resonates with the ‘picturesque,’ which once reflected economic and colonial entanglements; now, the Instagram aesthetic speaks to an era of communicative capitalism (Ngai; Dean). Within this aesthetic framework, Telašćica is confronted with what Jodi Dean calls a ‘whatever subject’ – a subject whose “whatever” signals a form of communication that lacks depth, a hollow connectivity that does not seek to understand itself beyond the bounds of perpetual sharing and display. In this sense, Telašćica becomes a “whatever” destination, an Instagrammable site for a ‘whatever subject,’ caught in a loop of visibility that obscures the very hegemonic discourses shaping its existence. As an Instagram Hot Spot, Telašćica is thus flattened, transformed into a consumable backdrop for a subjectivity that has been entrapped in the visual field.